Analysis of the performance of an oscillating propeller in cavitating flow. (15th September 2018) - Wang, Lianzhou; Guo, Chunyu; Xu, Pei; Su, Yumin
Abstract: During voyages, a ship will inevitably encounter wavy conditions that cause heaving motions. These motions induce oscillations in the propeller relative to its surrounding fluid, causing the propeller to operate in off-design conditions under non-uniform inflows. These environments-induced motions will significantly alter propeller performance. To study the motions of the propeller of a surface ship in wavy conditions during actual voyages, numerical simulations were conducted on an oscillating propeller in cavitating flows by using Reynolds-averaged Navier–Stokes (RANS) approach. The rotations and oscillations of the propeller were coupled using an independently defined set of equations of motion, with the oscillations being represented as sinusoidal cyclic motions. The numerical propagation of unsteady flow fields was obtained using the overset grid technique. This approach allowed the hydrodynamic behaviours of a propeller to be fully investigated in the presence of coupling between the rotations and oscillatory motions of the propeller. The effects of non-uniform incoming flows on a propeller's unsteady load and the distribution of sheet cavitation and wake field were analysed for two different loading conditions. The results of these calculations are significant for propeller design and optimization. Highlights: The numerical propagation of unsteady flow fields was realized via the overset grid technique. The propeller's rotations and oscillations were coupled using an independently defined set of equations of motion. The hydrodynamic behaviour of propellers in oscillatory conditions was investigated.